Hubungan Ketepatan Menggosok Gigi Dengan Karies Gigi Molar Pertama Permanen Murid Kelas V Dan VI SDN Sungai Landas Kecamatan Karang Intan Tahun 2023 - Aprilia, Irma; Kisworo Utami , Naning; Sab'atul Habibah, Siti; Isnawati, Isnawati (JURNAL TERAPIS GIGI DAN MULUT, 2024)
Dental and oral health is a problem that requires continuous handling. Most Indonesians have improper brushing habits. Most people in South Kalimantan are still not right in brushing their teeth about the right time to brush their teeth, namely the morning after breakfast and the night before going to bed The habit of brushing teeth can lead to dental caries. This study aims to determine the relationship between the accuracy of brushing teeth with permanent first molar caries for grade V and VI students of SDN Sungai Landas, Karang Intan District. The research design used was "cross sectional". The population in this study was 55 students and the study sample amounted to 55 students of grades V and VI of SDN Sungai Landas. The sampling technique used is Total Sampling. The technique used for data collection is by distributing questionnaires and analyzed using the chi-square test. The results of this study found that from 55 students in grades V and VI there were 43 students who had caries and only 8 students who did not experience caries. Based on chi-square analysis, stating that a p value of 0.000 < α (0.05) is obtained so that it is smaller than α = 0.05 then Ho is rejected and Ha is accepted. The conclusion of this study is that there is a relationship between the accuracy of brushing teeth with permanent first molar tooth caries of grade V and VI students of SDN Sungai Landas, Karang Intan District. It is recommended that the holding of UKGS activities in schools and through continuous counseling on dental and oral health can increase the knowledge of SDN Sungai Landas students.